Authorial self-representation in english research articles written by native english and Thai writers - Yotimart, Darunee (2018)
Research article writers need to express their stance (self-representation) in order to build their arguments. However, non-native English writers have been found to be facing this difficulty. Therefore, this study was conducted with the following objectives: (a) to identify the frequency distributions of stance linguistic features used by the native English and Thai writers across different rhetorical sections of research articles; (b) to describe how the native English and Thai writers express their stance in their research articles across different rhetorical sections of research articles; and (c) to discover the issues and challenges that might be faced by the native English and Thai writers in terms of self-representation expressions and international publication. The data were collected from a corpus of 60 research articles (RAs) in Applied Linguistics (AL), written by the native English and Thai writers and from interviewing eight university lecturers in AL working in Thailand. The data were analyzed using frequency analysis, keyword analysis, textual analysis and thematic analysis. Hyland’s model of interaction was used as a frame of analysis. The findings show that the native English writers were overt when promoting their authorial self-representation while the Thai writers were covert in the use of stance linguistic features. The lack of self-representational expressions among the Thai writers was largely due to the lack of exposure to the Anglophone rhetorical practices and writing requirements as well as linguistic deficits. This study has pedagogical implication whereby a sample of guidelines for improving the teaching of English writing courses at advanced level in Thailand was developed. Another implication of this study is the effort in raising awareness of the importance of authorial self-representation expressions in writing RAs for international publication.